Progress on Traditional Chinese Medicine nursing of peptic ulcer bleeding (消化性溃疡出血的中医护理研究进展) - HUANG Hairong (黄海荣); SHEN Linyan (沈林艳); TANG Zhongyin (唐忠银); GONG Xuan (龚璇); WANG Sheng (王声) (Association of Integrative Nursing, 2021)
Based on the literature review, this paper summarized the Traditional Chinese Medicine nursing of peptic ulcer bleeding from perspectives of emergency care, routine nursing and comprehensive nursing management, and provided reference for the improvement of Traditional Chinese Medicine nursing protocol for peptic ulcer bleeding. (本文通过查阅文献, 从急救护理、常规护理、综合护理等各方面对消化性溃疡出血的中医护理进行了综述, 以期为进一步完善消化性溃疡并出血的中医护理方案提供参考。)